EFEKTIVITAS PEMBELAJARAN OLAH TUBUH BAGI SEORANG PENARI (Sebuah Penelitian Tindakan Kelas) - Budi Setyastuti (Gelar : Jurnal Seni Budaya, 2012)
The aim of physical exercise learning is to prepare one’s body for being a dancer. Besides maximum quality in movement, a dancer also needs a strong body. Learning effectively is a must in view of limited time. To achieve effectiveness in physical exercise learning, data collection by observation and interview is needed. Technique of data processing is conducted by structure analysis covering a concept, method, approach, and theory. The research results show that physical exercise has used theory based on self-defense called karate since the beginning of 1980. A new method of physical exercise according to the dancer’s need is required. There are many steps in physical exercise such as warming up, movement variation and cooling down ; generally, all of them can be applied. Some movements which are compatible with a dancer’s demand need interpreting to make them more effective. It means the training takes less time but the result will support  the endurance of a   prospective dancer. Key words : physical exercise, effectiveness, dancer, method